The Limits of Social Media: What Social Media Can Be, and What We Should Hope They Never Become. (29th April 2015) - Srauy, Sam
Social media are among many tools that people use to articulate culture. However, it must be remembered that social media are websites that afford community building regardless of the morality, social benefit, or social detriment of the communities that get built. At their core, social media sites are products created by their respective corporations with the intent of monetizing the labor of their users. The values that these sites might offer are dependent on the users and the users' ability to claim some social benefit. In this regard, the author argues that social media can be beneficial spaces where society articulates and records culture "only if" users can maintain that use despite corporate actors' efforts to monetize users' labor.